Tinjauan Syariah Terhadap Praktik Jual Beli Online Dengan Dropshipping : Studi Kasus Mahasiswi Ekonomi Syariah STAI Imam Asy Syafii Pekanbaru Riau - Nita, Tesa Wirda; Kusuma, Febri (EL-EMIR Institute, 2025)
The advancement of digital technology has significantly transformed trade transaction patterns, including the emergence of online sales through the dropshipping system. In this business model, sellers act as intermediaries who forward customer orders directly to suppliers without holding inventory. From an Islamic economic perspective, this raises concerns regarding the validity of contracts (akad), ownership of goods, and the responsibilities involved. This study explores the practice of dropshipping from the perspective of fiqh muamalah, using a qualitative approach through a case study of Sharia Economics students at STAI Imam Asy-Syafi’i Pekanbaru Riau who engage in dropshipping activities. Data were collected through observation, interviews, and document analysis. The findings indicate that most participants lack understanding of Sharia-compliant contracts such as akad salam, wakalah, and istisna’. Moreover, some transactions contain elements of gharar (ambiguity/uncertainty), which may violate Islamic principles. To enhance Sharia compliance, this study recommends several measures: employing the salam contract with clear conditions and upfront payment, obtaining the supplier's permission before advertising products, granting khiyar (option) rights to buyers if goods are not as expected, and ensuring that sellers only offer products they legally own. These practices can help align dropshipping activities with ethical and legal standards in Islamic commerce.